Geovisualization for moderating urban heat island towards green city in Shah Alam / Haslam Hussain , Abdul Rauf Abdul Rasam and Zaharah Mohd Yusoff - Hussain, Haslam; Abdul Rasam, Abdul Rauf; Mohd Yusoff, Zaharah (2012)
Previous studies have shown that the presence of urban heat island (UHI) can affect metropolitan regions. The UHI is a phenomenon where the absorption of solar radiation by mass building structures, roads, and other hard surfaces during daytime, is subsequently re-radiated to the surroundings and increases ambient temperatures at night (Wong & Yu, 2005). This paper shows how to simulate a green area in Shah Alam for cooling UHI-spots using three geoinnovative methods; geovisualization, location analysis,and green city index. Geovisualization is the visual critical analysis and geospatial presentation using integral approaches from scientific and information visualization, image analysis, exploratory data analysis, and GIScience. Satellite land surface temperature (LST) and digitized topographical maps show that Section 21 recorded higher temperatures or is a UHI-spot (330C-340C). Based on the location analysis, the spatial characteristics of the spot are industrial areas, populous areas, and near to main roads. Clearly, the areas with fewer plants always have higher temperatures,indicatingthat the role of green areas is essential in moderating the UHI severity in the city. The concept of selected green city indexes and Malaysian tropical forest are adapted to produce a proposed green city in Section 21 Shah Alam. The green elements need to be implemented in the study area such as sustainable shopping complex and housing, systematic office and hotel planning, and other green space.